The Product Market Strategy, Value Creation, and Competitive Advantages as a Determinant Factor of Marketing Performance - Yusuf Abdullah; Ati Rosliyati (International Journal of Supply Chain Management, 2020)
The Micro-finance Industry occupied a strategic role in the Indonesian economy. Bank Perkreditan Rakyat (BPR) as one of the micro-finance institutions has an important role in encouraging the development of micro, small and medium enterprises (SMEs). Even the BPR still has obstacles, in terms of competition. The contribution of BPR nationally is only 4% compared with the contribution of commercial banks, besides that, the product market strategy was still carried out sporadically. It was not becoming a leading of a value creation strategy and competitive advantages, exactly creating a unique product, which is different than the competitor’s products. This paper has the characteristics of a product-market strategy, value creation and competitive advantage that is guested in affecting the performance of marketing significantly. The analysis used is descriptive analysis for qualitative variables and verification analysis for testing the hypothesis by using statistical tests. The analytical tool used is Structural Equation Modeling (SEM) that is the analysis unit was directors of microfinance institutions. The sample size was 300 respondents (directors of BPR in Indonesia) who are determined by the Stratified Random Sampling technique. The finding of this study states that the product market strategy, value creation, and competitive advantage positively affect marketing performance. The influence of value creation is greater than the effect of product market strategy to marketing performance. In order, to optimize marketing performance is still dominated by the product market strategies. Therefore, the BPR has to pay attention and enhance the value creation for raising the performance and profits.